Profil Status Gizi Anak Batita (di Bawah 3 Tahun) Ditinjau dari Berat Badan/tinggi Badan di Kelurahan Padang Besi Kota Padang: Profile of Nutritional Status of Toddlers (Under 3 Years) Based on Weight/Height in Padang Besi Urban Village, Padang City - Dwi Novrianda (Fakultas Keperawatan Universitas Andalas, 2015)
Nutritional problems are important issues that need to be even more so in the toddler because the mostvulnerable groups of nutrients. This study aims to assess nutritional status of toddlers (1-3 years) in terms ofweight / height at Padang Besi. The study was a descriptive study design. It was conducted from August 2010until April 2011. The samples were 109 people with proportional random sampling. Data analysis was done byunivariate using table of frequency distribution. The result showed 87,2 % nutrititional status was normal and12,8 % was low. It is expected that health workers in the health center to further increase the frequency of healthpromotion such as counseling on nutritional status of toddlers for knowledge, attitudes and actions of mothersabout nutrition for the better, and monitoring nutritional status of toddler to the Public Health Center.